Climate resilient urban areas. Governance, design and development in coastal delta cities. - (:unkn) unknown (Palgrave Macmillan, 2021)
This book describes the urgent challenge faced by cities worldwide to become resilient to climate change impacts. This challenge goes further than the ability to resist the impacts of extreme weather conditions. Coping with climate impacts and the ability to recover from them are equally important, as well as the capacity to adapt to the effects of climate change and the ability to transform the entire urban system. The book explores how the resilience journey for coastal cities in particular encompasses using scientific knowledge but also the knowledge of citizens and practitioners. Measures and strategies on different scales are needed, from national scale all the way down to neighbourhood, street level and building level. Representing the holistic nature of climate resilience, this collection contains unique insights from leading scientists and practitioners in areas of expertise such as engineering, social sciences and urban design.
Keywords: Küstengebiet; Klimawandel; Resilienz; Nachhaltige Stadtentwicklung; Hochwasserschutz; Klimaanpassung; Anpassungsstrategie; Mündungsgebiet; Flussmündung; Küstenstadt; Flussdelta